Optimal pressure for measuring objective lymphedema with postoperative ultrasonography in patients with breast cancer. (16th December 2016) - Lim, Chaiyoung; Hwang, Byungkwan; Park, Hee-Won; Lee, Do-Hong; Park, Ji-Eung; Lee, Kyu Jin; Kim, Sun Kwon; Seo, Kwan Sik
Abstract: Objective: To examine the reliability of ultrasonographic thickness and compressibility along with real-time pressure monitoring to evaluate postmastectomy lymphedema and to suggest a reference range of appropriate pressure. Design: Measurement reliability study. Setting: Research laboratory. Participants: Fifteen patients with prior mastectomy for breast cancer who were diagnosed with secondary lymphedema, and 16 healthy control subjects. Methods: The thickness and compressibility of the subcutaneous layer in the arms of 15 postmastectomy patients with secondary lymphedema were measured using B-mode and M-mode ultrasonography. An ultrasound machine was equipped with a real-time pressure-monitoring device to monitor downward compression pressure on the arms at a constant velocity. The ratio of thickness change defined the compressibility index. Two different experienced examiners participated in the measurement of lymphedema. Intrarater reliability and inter-rater reliability were estimated using the intraclass correlation coefficient. Very good reliability was defined as an ICC of more than 0.8. Main outcome measurements: The thickness of the subcutaneous layer, the compressibility index, and the intrarater and inter-rater reliability were measured. Results: The measured thicknesses demonstrated very good intrarater and inter-rater reliability for the forearm and upper arm. For the compressibility index, the upper arm and forearm had very good intrarater and inter-rater reliability at over 2000 Pa of compression (>0.9). Conclusions: Ultrasonography with real-time pressure monitoring may be useful for evaluating the severity and characteristics of lymphedema, particularly at compression pressures more than 2000 Pa.